Effect of nitrogen and temperature on phytomass production and essential oil yield of thyme - Hister, Carmine Aparecida Lenz; Andriolo, Jerônimo Luiz; Tedesco, Solange Bosio (Disciplinarum Scientia | Naturais e Tecnológicas, 2025)
Thyme (Thymus vulgaris) is extensive used in the food and cosmetics industries, as well as for its medicinal purposes. The objective was to evaluate the phytomass production of thyme plants grown in different seasons and with different nitrogen concentrations in the nutrient solution, as well as to calculate the essential oil yield. The experiments were conducted in a greenhouse between the years 2019 and 2020. Fresh mass was measured to calculate phytomass production, and essential oil production was analyzed for yield. The design used in the greenhouse experiment was entirely randomized, conducted in a factorial scheme (2X5), in two seasons of the year (winter and summer) and 5 nitrogen concentrations in the nutrient solution (5, 7, 9, 11 e 13 mmol.L-1). Data on fresh mass production and essential oil yield were compared by the Scott-Knott test and analyzed by polynomial regression, at 5% probability of error. The treatment with the highest nitrogen concentration in summer promoted the highest average dry mass per plant (34.95 g) and the highest essential oil yield (10.27%). Thus, the nitrogen, added to the nutrient solution, promoted an increase in the vegetative growth of thyme plants only when the temperature was high. The increase in phytomass of the plants promoted a higher essential oil yield.